Pengaruh Kepemimpinan Pelayanan, Kecerdasan Emosional Dan Komunikasi Interpersonal Terhadap OCB Pada Kantor Imigrasi Kelas 1 TPI Padang - Fitriadi, Yohan; Nugraha, Afif (Journal of Science Education and Management Business, 2022)
This study aims to examine the Service Leadership Method, Emotional Intelligence and Interpersonal Communication. The method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) 3.0. By distributing questionnaires as many as 65 respondents.The results of the data analysis concluded that there was no positive effect between the service leadership variable and the employee job satisfaction variable, and there was no significant effect. There is a big positive impact between the variable "Emotional Intelligence" and the variable "Job Satisfaction". Between interpersonal communication variables, there are positive and minor impacts on job satisfaction variables. There are positive and negligible impacts between service delivery variables for an organization's civic behavior variables. There is a significant positive effect between emotional intelligence variables for an organization's civic behavior variables. There is a positive and insignificant effect between interpersonal communication variables on organizational citizenship behavior. This study was explains that for the Immigration Office Tpi Class 1 Padang, the leadership is expected to be able to increase the application of harmonious and positive service leadership in order to increase employee motivation and self-confidence. In addition, employees are expected to continue to apply strong emotional intelligence so that employee performance at the company is more optimal